The integration of design and manufacturing using a design-with-features approach for turned components - Abdul Razak, Ariffin (Penerbit UTM Press, 1991)
This paper describes the work that has been done with an intention to integrate the design and manufacturing functions by developing a feature-based 'front-end' to a CAD solid mode11er. This enables designers to express their concepts in terms of manufacturing features and processes, and simultaneously captures this information in a form suitable for an outline process plan.